1999
DOI: 10.1111/j.1469-7998.1999.tb00767.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and territorial aspects of suckling behaviour in the domestic pig (Sus scrofa f. domestica)

Abstract: The suckling behaviour of 327 piglets from 39 litters of primiparous domestic sows Sus scrofa f. domestica was analysed regarding the development of territorial suckling consistency during a 5-week suckling period. Additionally, the consistent use of a certain teat pair (1±7) during the whole suckling period was related to weight gain within the suckling period and to social dominance after weaning and mixing of the piglets. The piglets increased their suckling stability consistent with a three-parametric expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Animals of both genotypes in the present study showed a high teat pair and udder region fidelity when observed, indicating that a stable teat order had been established by the age of 2 weeks. Udder region use has been linked to weight gain and dominance in piglets with animals suckling posterior teats tending to grow slower and being less dominant (Puppe and Tuchscherer 1999;Litten et al 2003). In the present study, GFP piglets do not appear to be disadvantaged in the access to the anterior udder region.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Animals of both genotypes in the present study showed a high teat pair and udder region fidelity when observed, indicating that a stable teat order had been established by the age of 2 weeks. Udder region use has been linked to weight gain and dominance in piglets with animals suckling posterior teats tending to grow slower and being less dominant (Puppe and Tuchscherer 1999;Litten et al 2003). In the present study, GFP piglets do not appear to be disadvantaged in the access to the anterior udder region.…”
Section: Discussionmentioning
confidence: 47%
“…A teat order study was performed 14 days of age as by then the teat order has been established and teat fidelity is high (Puppe and Tuchscherer 1999;Litten et al 2003). The piglets were individually numbered with a non toxic marker pen on forehead ( Supplementary Fig.…”
Section: Teat Order Lesion Assessment Resident/intruder Test -Sociamentioning
confidence: 99%
“…However, per kg body weight, milk consumption does not appear to differ between IUGR and normal-weight piglets (Rezaei et al, 2011). Offspring that obtain milk from anterior and middle mammary glands (MGs) grow faster than those suckling posterior MG (Puppe and Tuchscherer, 1999;Kim et al, 2000). Besides the greater amount of colostrum and milk from anterior and middle MGs (Gill and Thomson, 1956), we reported that components in colostrum and milk secreted by anterior and posterior MGs are also distinctive (Wu W.Z.…”
Section: Pre-weaning Growth Performancementioning
confidence: 85%
“…Piglets frequently change teats during the first hours after birth and, like kittens, demonstrate consistent individual use of particular nipples by day three but with a preference for anterior positions (McBride ; Hemsworth et al. ; Puppe & Tuchscherer ).…”
Section: The Suckling Contextmentioning
confidence: 99%